Overview of Burnout Among Nurses in Class 3 Inpatient Wards at Pekanbaru General Hospital - Aulya Nurfatiqoh; Niken Yuniar Sari; Tesha Hestyana Sari (Journal of Education Technology Information Social Sciences and Health, 2025)
Burnout is a condition characterized by emotional exhaustion, depersonalization, and a reduced sense of personal accomplishment experienced by nurses when caring for patients in hospitals. This condition negatively impacts nurses' performance in patient care and rehabilitation, and it can even increase the risk of medical errors that may endanger patient safety. This study aims to analyze the overview of burnout among nurses in the Class 3 inpatient wards at Pekanbaru General Hospital. The research design used is a descriptive study, involving 89 nurses working in the Class 3 inpatient wards, specifically in the Surgical and Medical inpatient units (Irna Surgikal and Irna Medikal), as respondents. The measurement tool used is the MBI-HS (Maslach Burnout Inventory-Human Services Survey). Data analysis was conducted using descriptive statistics to illustrate the burnout conditions experienced by nurses. Out of 89 respondents, 58 nurses (65.2%) experienced mild burnout, 22 experienced moderate burnout, and 9 experienced severe burnout. The most affected burnout dimension was personal accomplishment, with an average score of 22.08, categorized as low. This was followed by the emotional exhaustion dimension with an average score of 12.89 (low category), and the depersonalization dimension with an average score of 3.19 (low category). The severity of burnout among nurses is influenced by factors such as gender, age, education level, years of work experience, and position in the ward, with each factor contributing to the level of burnout in the nursing work environment.